Ceramic production in the Kur River Basin (Fars, Iran) during the middle to late second millennium bce: a geochemical and technological characterization. - Pincé, Possum; Braekmans, Dennis; Lycke, Sylvia; Vandenabeele, Peter (Wiley, 2019)
A total of 119 middle to late second millennium bce pottery samples from six sites in the Kur River Basin (Fars, Iran) were examined to characterize these ceramics and reconstruct their manufacturing technology and the origin of the primary materials. For this, a combined study of handheld XRF and thin‐section petrography was performed. The geochemical signatures of these ceramics were defined and interpreted in their archaeological and geological framework, resulting in the determination of different production processes and clay types used for four ceramic wares (Middle Elamite, Qaleh, Shogha and Taimuran) and the identification of possible outcrops used for Shogha–Taimuran production.
Keywords: non‐destructive XRF; ceramic petrography; ceramic production; middle to late second millennium bce; Kur River Basin (Iran)